Pemberdayaan Masyarakat di Padukuhan Kemadang Kulon Melalui Inovasi Pangan Lokal dan Strategi Pemasaran Olahan Singkong - Natania Regina Clarabella Serafina; Rachelia Dhita Zefanya Tambunan; Maria Fransisca Sri Maulidha; , Michael Limawan; Kevin Stevano Rianto; Yohanes Paulus Ardha Suban Koten; Vern Blythe OsaVern Blythe Osaze; Vernandes Ziliwu; Laurensia Novena Naia Lumingkewas; Dismas Persada Dewangga Pramudita (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2026)
This community service activity aims to empower women's groups of the Family Welfare Empowerment (PKK) in utilizing cassava (telo) as a valuable food ingredient through training in making steamed caramelized bingka telo. Cassava was chosen because of its high carbohydrate content ( 34.7g/100g) and potential for food product diversification. The method used was a participatory practical demonstration (70%) and theory (30%). Participants followed the steps of making bingka cake based on a predetermined local recipe, including the process of making sugar caramel and the steam-baking mechanism. The results of the activity showed an increase in participants' knowledge and skills in processing cassava into new products. The women were able to make caramelized bingka telo with a variety of flavors and attractive decorations. Additional activities such as selecting a product logo and planning a selling price also provided practical entrepreneurial experience. This program successfully increased local food production capacity and awareness of family economic values. With an innovative approach and sustainable support, it is hoped that similar activities can continue to be developed to improve family economies and food security based on local potential.